The Impact of Backspin Release Modes on Basketball Spin Axis Alignment - Madelyn Carniglia; Nathan Slegers (Journal of Coaching and Sports Science, 2025)
Background: Ball backspin is created during a basketball's final release. The complex nature of the hand-ball interaction at the moment of release can result in spin axis (SA) misalignment, which decreases shooting accuracy.Aims: This study is the first to analyze distinct backspin modes, such as hand orientation, twist, and push location, and how each mode contributes to overall SA misalignment.Methods: Three-dimensional ball backspin, hand orientation, hand position, and ball twist before release were measured for 20 male basketball athletes. The multiple linear regression test analyzed SA misalignment about the vertical axis (ey) and side SA misalignment (ez).Results: The multiple linear regression for SA misalignment about the vertical axis (ey) found that the orientation of the fingers and twist modes were equally important while the push location was insignificant (f2 = 1.9, R2 = 0.63, F = 17.0, p less than 0.001). For side SA misalignment (ez), all three modes contributed to ez misalignment (f2 = 3.3, R2 = 0.77, F = 18.1, p less than 0.001), with both the orientation of the palm and twist modes contributing equally and the vertical push location having a smaller contribution.Conclusion: This study demonstrates that five different backspin modes—two for ey and three for ez—each have distinct effects and combine to produce the final SA alignment after the ball is released. Knowing how each mode contributes to the final SA misalignment will allow coaches to identify necessary changes in individual players' shooting techniques to improve their release and increase accuracy.